Wide-band mid-infrared quantum devices based on intersubband transitions - Etienne, Rodriguez Martinez (2018)
The infrared region is the cradle of many vital applications in spectroscopy, medicine and communication. In the Mid-Infrared (MIR) region, innovations and significant improvements of the existing technologies call for advanced behaviour such as frequency comb lasers and high-speed photodetectors with high photoresponse at room temperature. Conventional systems are facing significant challenges due to their intrinsic high-speed limitations and the complexity to reach this domain. The development of quantum devices based on Intersubband Transitions (ISBT) has revealed significant advantages in the MIR reviving intense research in these fields. They allow excellent efficiency in the MIR region, and due to their structures based on quantum wells, they permit an easy tunability of the operation wavelength. In comparison to conventional devices, ISBT exhibits a very short carrier lifetime which makes them suitable for high-speed applications. The objective of this thesis is to develop and study the high-speed behaviour of quantum devices based on intersubband transitions for emission and detection of coherent light in the MIR region. Additionally, thanks to their wide-band properties, frequency combs and injection locking of Quantum Cascade Laser (QCL) using radio-frequency excitation will be investigated. In this thesis, we first present the context, and why MIR region is critical for many applications, then we will develop the theory of quantum cascade laser, frequency comb lasers and quantum well infrared photodetector using the unique properties of intersubband transitions. Secondly, we will give an overview of the process and standard characterisations of QCL devices and then investigate their high-speed behaviour using rectification methods. Using high-frequency setups, we will study the influence of a Radio Frequency (RF) injection at the round-trip frequency on the spectra, especially the generation of sidebands in the optical spectrum for QCLs in the two windows atmospheric (MWIR and LWIR). We will then investigate the injection-locking mechanism and, using high-resolution FTIR, analyse the Free-Spectral Range of the spectrum with and without RF injection. In the third part, we will develop a Quantum Well Infrared Photodetector (QWIP) based on air-bridge contacts to promote the high-speed modulation. Optical characterisation of the devices has been realised to deeply understand the dependence of the responsivity and photoconductive gain with the temperature and high electric field. Finally, we tested its wide-band operation by detecting the high-frequency modulation of the QCLs previously characterised. The development of both high-speed emitter and receiver at the same wavelength allow a powerful pair for many applications in the MIR region.